Studi Kasus Aktivitas Pertambangan Batuan terhadap Kondisi Lingkungan Sungai Bolango - Suryadi Syamsuddin; Dewi Wahyuni K. Baderan; Fitryane Lihawa (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
Rock mining along the Bone River, Bone Bolango Regency, contributes to infrastructure development but also has negative environmental impacts. This study aims to analyze the effects of mining activities on river environmental quality, particularly water discoloration, erosion, river widening, and material accumulation. Data obtained indicate that mining activities cause water pollution characterized by discoloration due to increased sediment and mining waste. Moreover, rock excavation accelerates erosion along riverbanks, resulting in land degradation that affects the stability of surrounding areas. Mining activities also trigger river widening, altering the river's natural morphology and increasing flood risks. The accumulation of mining residues around the river worsens conditions by obstructing water flow, causing sedimentation, and damaging aquatic habitats. The analysis highlights the need for better environmental management to mitigate the adverse effects of rock mining. Recommendations include implementing strict environmental policies, monitoring mining operations, conducting reclamation, and ensuring sustainable waste management. Additionally, involving local communities in river rehabilitation efforts can expedite environmental recovery and sustain ecosystem balance. This study is expected to serve as a reference for policymakers in managing mining activities sustainably and preserving the Bone River ecosystem.